The Husserl-Heidegger relationship in the Jewish imagination - Herskowitz, D (University of Pennsylvania Press, 2020)
This essay examines ways in which the troubled personal and philosophical relationship between the philosophers Edmund Husserl and Martin Heidegger was imagined, retold, and deployed in Jewish contexts. Focusing on the typological structures animating its reception, it argues that different narratives and ideological commitments concerning Judaism and Jewishness are absorbed in retellings of the Husserl-Heidegger episode. As such, these retellings offer a portal into major concerns in twentieth-century European Jewish thought and existence.